FORMATION OF MUNICIPAL HEALTH POLICY: AN ADAPTIVE APPROACH - Demchyshyn, Yaroslav (Public Management and Policy, 2026)
The article explores the process of developing an adaptive municipal health policy in Ukraine amid wartime challenges, digital transformation, and European integration reforms. Based on an interdisciplinary approach, it analyzes key concepts of modern governance – adaptive governance, complex adaptive systems, and the agile approach in the public sector. The study finds that the effectiveness of municipal health policy is ensured through a combination of flexibility, decentralization, digitalization, and partnership among the state, communities, businesses, and civil society. Particular attention is paid to analyzing the experience of Ukrainian municipalities during the war, which demonstrated institutional learning, crisis management, and digital coordination of medical services. The influence of European integration processes on the modernization of local health systems, legislative harmonization, implementation of European quality standards, and development of partnership programs with cities of the European Union is examined. A conceptual model of adaptive management is proposed, combining the principles of resilience, inclusiveness, and innovation. The results of the study have both theoretical and practical significance for developing strategies for the recovery and advancement of municipal health policy in Ukraine, focused on patient-centered care, quality, and sustainable development within the context of European integration.